Performance of Rice Tungro Resistant Promising Line in Endemic Area - Muliadi, Ahmad - (Informatika Pertanian, 2015)
Tungro disease is one of the important diseases of rice because it has a high potential for causing damage. The use of varieties resistant to the tungro disease effectively prevent an explosion tungro disease. Testing of promising lines resistant to the tungro at several locations is a stage in the breeding program before a line is released as a new variety that has resistance to tungro disease, as well as having the potential for high yields and good adaptation at several locations. Six of tungro resistant promising line (OBSTG02-137, OBSTG02-124, OBSTG02154, OBSTG02-130, OBSTG02-56, dan OBSTG02-37) and four check varieties (Inpari 9 Elo, Tukad Unda, Ciherang, and IR64) were evaluated for their yield potential and adaptability at 16 locations in tungro endemic area during the dry season of 2011-2013. The experiment was arranged in a randomized block design with 3 replications. Each line were transplanted in 4 m x 5 m plot size with plant spacing 25 cm x 25 cm. Observation were made on yield, 50% flowering date, plant heights, panicle number per hill, number filled and unfilled spikelets per panicle, and weigh of 1000 grains in gram. The results showed that effect of genotype x location interaction was significantly different for all component observed. Based on the performance of grain yield and yield components obtained, four lines i.e. OBSTG02-137 (6.74 t/ha), OBSTG02-124 (6.20 t/ha), OBSTG02-154 (6.37 t/ha ), and OBSTG02-130 (5,92 t/ha) has a high yield with the support of filled grain number and weight of 1000 seeds is high. Based on the combined value of bi and the general average of yield, then line OBSTG02-137, OBSTG02-154, and OBSTG02-130 were suitable to adapt to all environments, OBSTG02-124 is adapted in an optimal environment, OBSTG02-56 and OBSTG02-37 were adapted to the less productive environment.